What is the minimum change in left ventricular ejection fraction, which can be measured with contrast echocardiography? - Tan Suwatanaviroj; Weimin He; Edith Pituskin; Ian Paterson; Jonathan Choy; Harald Becher (Echo Research and Practice, 2018)
Background: There are limited data on what is the minimum change that can be detected in cancer patients undergoing treatment with cardiotoxic drugs and are referred for monitoring left ventricular (LV) function. Objective: To assess the variability in the measurement of LV volumes and ejection fraction (EF) in contrast echocardiography and to determine the minimum detectable difference (MDD) between two EF measurements that can be deemed significant. Methods: A total of 150 patients were divided into three groups according to EF (EF <53, 53–60, and >60%). Each group consisted of 50 randomly selected cancer patients who underwent contrast echocardiography between July 2010 and May 2014. Repeated measurements of LV volumes and EF were performed offline by a sonographer and a cardiologist. Inter-observer variability was assessed by analysis of variance. Measurement error was estimated by standard error of measurement and MDD. Results: The 95% confidence interval with a single measurement of EF was 2 percentage points in the groups of patients with EF <53% and EF >60%, and 2.5 percentage points for patients with EF 53–60%. The MDD for EF, end-diastolic volume and end-systolic volume that could be recognized with 95% confidence interval were 4 percentage points, 7 mL and 4 mL, respectively. Conclusion: Contrast echocardiography is a reliable tool for serial measurements of EF to monitor cardiotoxicity due to chemotherapy. In a high-volume echocardiography laboratory with experienced staff, the MDD for EF of 4 percentage points on a good-quality recording demonstrates the high reproducibility of the Simpson’s method using contrast echocardiography.